Strength of motivation among medical students in a private Malaysian medical school / Gauri Krishnaswamy - Gauri, Krishnaswamy (2019)
Over the last two decades, the importance of motivation in academic success has been on the rise, acknowledging the void in medical education. However, a lack in research on the factors influencing motivation among medical students in Malaysia still exists. The aim of this project is to analyse the strength of motivation among medical students in a private Malaysian medical school. The validated and reliable, revised version of the Strength of Motivation for Medical School (SMMS-R) questionnaire, was used for this research project. The participants consisted of medical students from Year 1 to Year 5 of a private Malaysian medical school. In conclusion, the pattern of strength of motivation saw two groups of students, those who were motivated to succeed academically and those who were not, though the number was negligible in the latter group. Students entered the medical programme with a high level of motivation which increased at a fairly constant rate over the years. Though females were seen to have a higher motivation level it was not a significant finding. The results did not show any relationship between level of strength of motivation and educational background. Lastly, the cumulated grade point average (CGPA) was not a predictor of motivation as there were students of moderate to strong motivation among the low CGPA results group. This work may inform policies and guidelines, and influence medical educators that students’ motivation levels should not be concluded based on age, gender, high school examination scores or educational background. Furthermore, it addresses the gap in knowledge about motivation among medical students in Malaysia.